Teaching Techniques Used by Secondary School Teachers During Implementing of the Competency-Based Curriculum in Namtumbo District Ruvuma Region (American Journal of Arts and Human Science, 2025)
This study investigates the teaching techniques used by secondary school teachers during implementing of the Competency-Based Curriculum in Namtumbo district. This study was carried out at Namtumbo district located in Ruvuma Region, Tanzania. This study used pragmatism paradigm since the study used mixed methods research approach where both qualitative and quantitative approaches was used. This study used convergent research design where quantitative and qualitative data was collected at the same time, analyzed separately. The study used a sample size of 152 informants from a population of 496. Qualitative data recorded from interview whose contents summarized in a narrative format while quantitative data analyzed using descriptive statistics. Finding show that, 87.9% a significant majority of teachers frequently use interactive techniques in implementing CBC such as group discussions, demonstrations, and question-and-answer sessions to inspire active learning and teamwork. Also, techniques like surveys, project, practical and lectures are less common used due to limited resource and time constraints. Moreover, study concluded that, in student’s assessment, utmost 88.7% of teachers regularly use techniques such as quizzes and tests, while project-based and practical assessments is crucial for practical skill development are less often used in assessment due to inadequate teaching and learning resources. However, oral and practical assessments are common, demonstrating a balance among traditional and modern assessment approaches. Teachers’ commitment to active student participation, evident from the high use of participatory techniques 97.2%, increases CBC’s efficiency by encouragement an interactive, competency-focused learning setting where consistent response and guidance are integral, mainly in practical activities. Study recommend for schools to priorities time and learning and teaching resources for practical and project-based learning in order enhance resource allocation.